Lifestyle behaviors, social and economic disadvantages, and all-cause and cardiovascular mortality: results from the US National Health Interview Survey - Duarte Junior, Miguel Angelo; Pintos Carrillo, Salud; Martínez-Gómez, David; Sotos Prieto, Mercedes; Rodríguez-Artalejo, Fernando; Cabanas Sánchez, Verónica (Frontiers in Public Health, 2024)
Aim To examine the independent relationships of lifestyle and social and economic factors with all-cause and cardiovascular disease (CVD) mortality in a large representative sample of the US adult population. Furthermore, the association between the combination of lifestyle and social and economic factors with mortality was analyzed in detail. Methods The sample included 103,314 participants with valid records and eligible for mortality follow-up, and information on lifestyle factors and social and economic disadvantages (NHIS waves 2000, 2005, 2010, and 2015). An unhealthy lifestyle score was constructed using information on physical activity, alcohol consumption, diet, and smoking status. Social and economic disadvantages were assessed using information on education, receipt of dividends, employment, family's home, and access to private health. Information on mortality data was determined by the National Death Index records. Results Compared with favorable lifestyle, unfavorable lifestyle was associated with higher all-cause (HR 2.07; 95% CI 1.97–2.19) and CVD (HR 1.84; 95% CI 1.68–2.02) mortality. Higher social and economic disadvantages were also associated with higher all-cause (HR 2.44; 95% CI 2.30–2.59) and CVD mortality (HR 2.44; 95% CI 2.16–2.77), compared to low social and economic disadvantages. In joint associations, participants in the high social and economic disadvantage and unfavorable lifestyle showed a greater risk of all-cause (HR 4.06; 95% CI 3.69–4.47) and CVD mortality (HR 3.98; 95% CI 3.31–4.79). Conclusion Lifestyle and social and economic disadvantages are associated with all-cause and CVD mortality. The risk of mortality increases as the number of social and economic disadvantages and unhealthy lifestyles increases.